2003
DOI: 10.3354/meps249025
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance and subsequent recovery of mid-shore assemblages on seasonal, tropical, rocky shores

Abstract: Hong Kong experiences a strongly seasonal climate, with distinct hot, wet summers and cool, dry winters, which has a great influence on intertidal assemblages. The impacts and relative importance of disturbance events on assemblage structure and subsequent recovery in this environment were examined on semi-exposed rocky shores. In August 1997, Typhoon Victor affected Hong Kong coastal waters bringing high seas and strong winds. Effects on mid-shore assemblage structure were patchy, with an increase in free spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…More common and generalist species in both areas, however, exhibited rapid recovery and some species even increased in abundance. While initial mortality is high from storm surges, due to turbulence and low dissolved oxygen, estuarine fishes are mostly resilient to saltwater storm surges and recover to preimpact conditions within 4-6 weeks (Hutchinson and Williams 2003;Paperno et al 2006;Stevens et al 2006). Freshwater fishes in the downstream reaches (e.g., centrarchids) also exhibited an ability to withstand storm surge impacts.…”
Section: Discussionmentioning
confidence: 99%
“…More common and generalist species in both areas, however, exhibited rapid recovery and some species even increased in abundance. While initial mortality is high from storm surges, due to turbulence and low dissolved oxygen, estuarine fishes are mostly resilient to saltwater storm surges and recover to preimpact conditions within 4-6 weeks (Hutchinson and Williams 2003;Paperno et al 2006;Stevens et al 2006). Freshwater fishes in the downstream reaches (e.g., centrarchids) also exhibited an ability to withstand storm surge impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Connell and Slatyer, 1977;Sousa, 1979;Paine and Levin, 1981;Van Tamelen, 1996;Chapman and Underwood, 1998) and there is a rich literature describing such successional changes in detail in a wide variety of coastal marine ecosystems (e.g. rocky shores: Kim and DeWreede, 1996;Benedetti-Cecchi and Cinelli, 1996;Dye, 1998;Williams et al, 2000;Hutchinson and Williams, 2003;coral reefs: Connell et al, 1997;Diaz-Pulido and McCook, 2002; soft sediments: Levin and DiBacco, 1995;Rosenberg et al, 2002;estuaries: Nogueira et al, 2000;salt-marshes: Valiela, 1995;Levin et al, 1996;Craft and Sacco, 2003) from all over the world. These studies have demonstrated that succession is likely the composite result of several processes (depletion, tolerance, facilitation, inhibition, removal, allelopathy, etc.) that determine if replacement takes place (Connell and Slatyer, 1977) and at what rates it is accomplished (Valiela, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…To go one step further, the long-term effects of extreme events could be studied. Since rocky shores are highly dynamic systems, recoveries are expected to occur relatively fast, within months or few years [71,72]. Therefore, the temporal scale to monitor in rocky shores should be adapted to this temporal scale, and several samplings should be done within the year to embrace seasonal variation of this ecosystem.…”
Section: Long-term Effectsmentioning
confidence: 99%